INCIDENCE OF PSYCHOSOCIAL HEALTH DISTURBANCES AMONG NONMEDICAL TRAMADOL USING EMERGING ADULTS IN OWERRI, IMO STATE - Ukachi Madukwe, Ann (African Journal of Social and Behavioural Sciences, 2024)
This study screened twenty-eight (18 male & 10 female) emerging adults aged 16 -27 years selected from a normal population, who had used tramadol for at least one month. Respondents were drawn through the snowball sampling method. The Tramadol Questerview and Drug Use Screening Inventory-Revised were used to evaluate respondents’ non-medical use of tramadol and the severity of psychosocial health disturbances, respectively. The study adopted a descriptive design and descriptive statistics were used to analyse data. Findings showed that respondents had significant overall problem density ranging from 24.48 at the lowest to 67.34 at the highest. Tramadol use was associated with significant absolute and overall problem densities in the six domains of psychosocial health screened. Also, 80.8% of the respondents used 200mg to 600mg day daily, and dosage per day was significantly associated with the health status domain. The study concluded that long-term nonmedical misuse of tramadol has a negative impact on the psychosocial health of young persons. It is recommended that tramadol should remain scheduled as a controlled drug in Nigeria; and be prescribed in rare cases and for very short therapy periods for older persons.